Expeditious Synthesis of Fluorescent Bis(phenylfuryl)benzenes - Zhang, Miao; Wang, Tingshu; Boo, Chanyoung; Koo, Sangho (Synthesis, 2022)
Versatile fluorescent polyaromatic compounds of alternating benzene and furan rings, para- and meta-bis(5-phenylfur-3-yl)benzenes, were expeditiously synthesized by double Mn(OAc)3-catalyzed oxidative decarbonylation and Paal–Knorr reactions of β-ketoesters, prepared from the conjugate addition of ethyl acetoacetate to para- and meta-bis(chalcones). Stronger fluorescence intensity was observed for meta-bis(phenylfuryl)benzene with ortho-methoxy substitution, whereas longer fluorescence wavelength was observed for para-bis(phenylfuryl)benzene with para-methoxy substitution.
Keywords: arenes; cyclization; radical reactions; fluorescence; manganese